Supplier Excellence - Case Vacon Oyj - Hermans, Johanna Emilia (My University, 2012)
Globalization has been a routine during the last decades almost in all business areas. Supply chain management and purchasing has become one of the biggest competitive advantages. Companies are more and more specialized on their own core competences and buy the products which other can manufacture better. This study gets together tools and methods which make easier to manage supplier chain from suppliers processes up to customer including standardized model for new part approval, quality management and every day operative actions with suppliers. The case organization is Vacon Oyj. Theoretical framework of study includes theories and principles about supplier selection and evaluation, supplier management and supply chain management. I will go through theories related to quality management, quality assurance and problem solving. Theoretical framework includes also process management and production management theories and principles following the principles of continuously improvement and lean. The study is qualitative study focusing on the literature of the world class methods and internal and external interviews. In the empirical part, I will also go through the implementation and standardization of tools and methods. Besides the numerical results this study produced a documented standard for supplier management which is implemented to all key suppliers. It will be implemented also globally to the other factories of the case organization.
Keywords: Supplier; supplier management; quality management; lean; fi=Tuotantotalous|en=Industrial Management|